IMPLEMENTASI APLIKASI JAKARTA KINI (JAKI) DALAM MEWUJUDKAN SMART CITY DI UNIT PELAKSANA TEKNIS JAKARTA SMART CITY - Zubaida, Dinda; Megawati, Suci (Universitas Negeri Surabaya, 2023)
In order to overcome city problems due to urbanization that continues to occur and is not controlled which includes issues of security, environment, health, energy, public services, and other city problems, the Jakarta city government has begun to launch the Jakarta Kini application program (JAKI) through the Jakarta Technical Implementation Unit. Smart City which is regulated in DKI Jakarta Governor Regulation No. 144 of 2019 concerning the Organization and Work Procedure of Communication, Informatics and Statistics Office of DKI Jakarta Province. The Jakarta Kini Application Program (JAKI), which is a program that integrates public service features in Jakarta and is also a one-stop integrated service that can provide benefits to its citizens which can be accessed online through the JAKI application on smartphones. The aim of the JAKI application program is to make it easier for the public to get information about Jakarta and to make it easier to access public services in Jakarta because it has been integrated through the application. This type of research uses a qualitative and descriptive approach. The focus of this research is the size and objectives of the policy, resources, characteristics of implementing agents, implementor dispositions, inter-organizational communication, and social, political, and economic conditions. Methods of data collection using interview techniques, observation, and documentation were analyzed using data analysis techniques consisting of data reduction, data presentation, and drawing conclusions.